2015
DOI: 10.1086/681556
|View full text |Cite
|
Sign up to set email alerts
|

Benefit-Cost Analysis of Crime Prevention Programs

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The University of Chicago Press is collaborating with JSTOR to digitize, preserve and extend access to Crime and Justice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 106 publications
0
32
0
Order By: Relevance
“…It was often argued that the best predictor of (criminal) behavior is previous (criminal) behavior, and adult offenders are thought to have a long history of delinquent behavior. Therefore, intervention strategies are mainly aimed at early prevention of juveniles (for a review, see e.g., [67]) and are regarded the most cost effective [24]. The substantial amount of adult-onset offenders found in this study suggests that early prevention strategies should be complemented by a focus on those with a late onset, especially to reduce the total number of offenders.…”
Section: Conclusion and Discussionmentioning
confidence: 91%
“…It was often argued that the best predictor of (criminal) behavior is previous (criminal) behavior, and adult offenders are thought to have a long history of delinquent behavior. Therefore, intervention strategies are mainly aimed at early prevention of juveniles (for a review, see e.g., [67]) and are regarded the most cost effective [24]. The substantial amount of adult-onset offenders found in this study suggests that early prevention strategies should be complemented by a focus on those with a late onset, especially to reduce the total number of offenders.…”
Section: Conclusion and Discussionmentioning
confidence: 91%
“…From a public policy perspective, developmental prevention programs can be quite effective and efficient, as their initial costs are often much less than the costs of later serious offending and they have monetary benefits beyond crimes reduced. Indeed, recent benefit–cost analyses of developmental prevention programs have revealed developmental prevention as a valuable strategy to save money and improve long‐term positive gains (Welsh, Farrington, & Raffan Gowar, ). For future work, this focus calls for more replication of existing developmental intervention efforts, roll out and dissemination, and the adoption of a developmentally informed public health approach to SYV.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Welsh and Farrington (2000a) reviewed 26 BCAs and concluded that the monetary benefits outweighed the monetary costs for three of the four principal crime‐prevention strategies (developmental, situational, and correctional intervention). More recently, Welsh, Farrington, and Raffan Gowar () updated the earlier reviews of BCAs of developmental, situational, and community prevention, and once again, they found that the monetary benefits usually outweighed the monetary costs.…”
Section: How Careful Rigorous Benefit–cost Analyses Made the Case Fomentioning
confidence: 99%